Peran Kompetensi, Motivasi dan Kepemimpinan Dalam Peningkatan Kinerja Pegawai - I Gede Ngurah Astawan; I Gusti Ngurah Putra Suryanata (Universitas Pendidikan Nasional, 2020)
ABSTRACTThe hospital is a capital intensive organization, full of human resources, solid technology and science, and regulation intensive. Solid capital because it requires a high investment to meet the requirements of both physical buildings and other supporting facilities and infrastructure, especially existing health equipment. Solid human resources because in hospitals work a variety of professionals / multidisciplinary with a large number of employees and demanded harmonious cooperation between professionals (team work) to create quality services. Health care providers in the world of health business are increasingly guided to be able to help fast and encouraged services capable of always developing and adapting to changes to win the competition. The purpose of this study is 1) To analyze and explain the influence of leadership, competence, motivation on employee performance and the role of variable motivation to work motivation. The method used in this study is a quantitative method with path analysis techniques. The results of the study show that 1) The competence on leadership in the Amerta Wing Installation of Sanglah Hospital Denpasar is equal to 0.270; 2) The direct influence of competence on leadership is at the Amerta Wing Installation in Sanglah Hospital, Denpasar, at 0.484; 3) Direct influence of leadership on employee performance at the Amerta Wing Installation at Sanglah Hospital Denpasar, amounting to 0.298; 4) The indirect effect of work motivation on performance in the Amerta Wing Installation at Sanglah Hospital Denpasar is equal to 0.080; 5) The indirect effect of competence on performance in the Amerta Wing Installation of Sanglah Hospital Denpasar is equal to 0.144; 6) The leadership role in mediating the influence of leadership on the performance of employees at the Amerta Wing Installation in RSUP Sanglah Denpasar shows that getting t count is = 0.208, and is significant with a value of 0.417 > 0.05 so it can be concluded that there is insignificant positive influence mediating work motivation between the influence of leadership on employee performance; and 7) The role of motivation in mediating the influence of competencies on employee performance at the Amerta RSUP Sanglah Denpasar Upper Installation shows that getting t count is = 0.207 and is significant with a value of 0.417 > 0.05 so it can be concluded that there is no positive effect significant mediation of work motivation between the effect of work competency on employee performance.